O nieprzedstawieniach i twórczości. Raport z wstępnych badań nad abstrakcją w aktualizowaniu i stymulowaniu twórczego myślenia u dzieci w wieku wczesnoszkolnym - Iwona Tomas (Problemy Wczesnej Edukacji)
This article is a report on the planned and conducted series of experimental art classes dedicated to children in early school age. The aim of the presented initial research was the verification of a working hypothesis assuming the positive influence of a planned and conducted art lesson class cycle inspired by abstraction, on the creative potential of the participants. In the research project presented and described below, abstraction has been treated as a potential factor stimulating creative thinking, the level of which has been identified by using Drawing Creative Thinking Test by K.K. Urban and H.G. Jellen (TCT-DP) in pre and post-experimental version. The research project was implemented on the basis of a quasi-experimental method, however – which must be emphasized – it has been based on the assumptions of action research and constructed on the basis of the ARTography category. 64 students from the first grade and two second grades of a primary school participated in the experimental class cycle. 47 pairs of drawings created on the basis of TCP-DP sheets have been analyzed and assessed. As a consequence, the distinguished working hypothesis has been initially confirmed – however, the presented research field requires further research, exploration and detailed analyses. The presented research and its initial results constitute a factor initiating the considerations regarding the possibility of applying and implementing non-standard solutions in art lessons, which – as it turns out, end up being solutions that are enriching and desirable, especially from the creative thinking perspective.